Anita M. Mallinckrodt: The Environmental Dialogue in the GDR. Literature, Church, Party, and Interest Groups in Their Socio-Political Context - Timm Menke (GDR Bulletin, 1992)
Lanham: University Press of America, 1987. 198 p.